Correction to: Policy uncertainty, derivatives use, and firm-level FDI. Issue 2 (February 2018) - Nguyen, Quang; Kim, Trang; Papanastassiou, Marina
Abstract Since this paper was first published, the publisher has been informed of an additional contributing author that should have been included. The authorship has now been corrected online, and the author's biographical sketch has been added. No other changes have been made to the text.